Investigation of a centimeter-scale leds based indoor visible light positioning system using a phase-shift measurement method - Li, Xiaofei (2017)
Indoor positioning systems (IPSs) provides the location information of devices and persons. Light Emitting Diode (LED) offers better properties such as energy efficiency, high brightness, and long life span. An indoor visible light positioning system utilizing the existing LED lights is achievable by modulating the positioning information into the LED light. In this project, LEDs arrangement factor affecting the positioning result are considered. A total of four different kinds of LEDs arrangement patterns is examined by simulation. A phase-shift measurement based positioning method with improved positioning accuracy is investigated. The positioning system with 3 LEDs is used in the experiment. This positioning method has the positioning error down to 5 cm, as shown with experiment measure, which is highly satisfactory.